Organic Nanoparticles in Anti-angiogenic Cancer Therapy - Mukherjee S.; Madamsetty V.S. (My University, 2025)
Cancer is still playing significant global health concern despite recent remarkable advances in the research field (K.I. Alcaraz, T.L. Wiedt, E.C. Daniels, K.R. Yabroff, C.E. Guerra, R.C. Wender, Understanding and addressing social determinants to advance cancer health equity in the United States: a blueprint for practice, research, and policy, CA: a cancer journal for clinicians 70(1) (2020) 31–46.;Najafi et al. in Journal of biochemical and molecular toxicology 35, 2021; G. Bor, I.D. Mat Azmi, A. Yaghmur, Nanomedicines for cancer therapy: Current status, challenges and future prospects, Therapeutic delivery 10(2) (2019) 113–132.;). © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.